Response to “Issues of Academic Support and Performance of Division I Student-Athletes: A Case Study at the University of Minnesota” - Callahan, Carolyn M. (Journal of Intercollegiate Sport, 2008)
“Issues of Academic Support and Performance of Division I Student-athletes: A Case Study at the University of Minnesota” (Kane, Leo, & Holleran, 2008) describes the process used by the University of Minnesota to examine the current state of academics and make data-based recommendations for the improvement of academic support for student-athletes. This paper serves as a benchmark paper for university administrators, faculty, and athletics departments. Many universities have undertaken self-examination in parallel efforts, but few have either documented their process and/or been willing to publicly share the process or the data. The papers’ authors provide important insights into the factors leading to meaningful examination of the issues and the politics leading to significant changes. Too often, in program evaluation (which this study truly was), the investigator fails to incorporate the necessary steps to ensure the identification of the appropriate questions, to gather data to adequately address critical questions relating to decision making, or to strategically include the decision makers who ultimately have the responsibility and the power to implement recommendations. To that end, the work of the University of Minnesota is a model for such a process. Hence, identifying and extracting model processes and examining those processes for ways to improve them can serve to guide others who have similar goals for their athletics programs.